1961
DOI: 10.1039/jr9610002276
|View full text |Cite
|
Sign up to set email alerts
|

442. The chemistry of the bile pigments. Part IV. Spectro-photometric titration of the bile pigments

Abstract: Spectrophotometric titration curves of four main types of bile pigments and related dipyrryl compounds reveal a predominantly basic character in urobilins, violins, and verdins, the basic strengths decreasing in that order, and a predominantly acidic character in rubins. Implication of these results on the structure of the pigments is discussed.ALL naturally occurring bile pigments contain carboxyl groups, separated from the main chromophores by two methylene groups, so that their ionisation is not detectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…(XV) (XVI) basic pyrrolenine nitrogen atom within the chromophore. The base strength decreases in the order shown, as found by spectrophotometric titration studies (Gray et al 1961). It appears therefore that the base strength decreases with increasing length of conjugation and the extent of this can, in turn, be assessed from the position of the visible absorption maximum.…”
Section: Vol 117 275supporting
confidence: 66%
See 1 more Smart Citation
“…(XV) (XVI) basic pyrrolenine nitrogen atom within the chromophore. The base strength decreases in the order shown, as found by spectrophotometric titration studies (Gray et al 1961). It appears therefore that the base strength decreases with increasing length of conjugation and the extent of this can, in turn, be assessed from the position of the visible absorption maximum.…”
Section: Vol 117 275supporting
confidence: 66%
“…Preparation of crude me8obiliviolin and glaucobilin (Gray et al 1961). The petroleum extract of crude mesobilirubinogen from the reduction of bilirubin (100mg) was evaporated to dryness.…”
Section: Methodsmentioning
confidence: 99%
“…However, precipitation of pigment, causing breaks or inflections in the titration curves, is a major problem with these methods, and spectrophotometric titrations are further complicated by autoxidation and aggregation of bilirubin and by the requirement for accurate extinction coefficients for the unionized and ionized forms of the pigment in water, which are not available. Using the spectrophotometric method, Gray et al (5) were unable to obtain accurate pK a values for bilirubin, but Moroi et al (11) found values of 6.1-6.5 for pK a1 and 7.3-7.6 for pK a2 , ascribing these remarkably high values, without explanation, to intramolecular hydrogen bonding (11). In contrast, using similar methods, Kolosov and Shapovalenko (9) estimated pK a1 and pK a2 for bilirubin to be 4.5 and 5.9, respectively.…”
mentioning
confidence: 99%
“…Titration of bilirubin in aqueous solutions suggests a pK value of 7-8. 42 Since bilirubin tends to form insoluble aggregates below pH 8.0, determination of pK by titration of aqueous solutions of bilirubin can be misleading. 37 The pK values for bilirubin have been determined by 13 C nuclear magnetic resonance spectra, and potentiometric and spectrophotometric titrations in aqueous solutions.…”
Section: Chemistry Of Bilirubinmentioning
confidence: 99%